2017
DOI: 10.1016/j.cplett.2017.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Observation of excited state absorption in the V-Cr Prussian blue analogue

Abstract: We present femtosecond transient transmission measurements of thin films of the V II/III -Cr III Prussian blue analogue (V-Cr PBA) in the spectral range 330−675nm after exciting the ligand-to-metal charge-transfer transition (LMCT) at 400nm. A global analysis including three decay-times of τ1=230fs, τ2=1.38ps and τ3>>2ns could satisfactory describe the data. We observed an excited state absorption (ESA) at 345nm, which was attributed to a chargetransfer transition from the 2 E state on the Cr ions after fast i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The signal decayed and reached a plateau within a few ps. In a later TA study with improved time-resolution, 149 it was shown that the GSB decayed with ca. 200 fs and 1 ps time constants to the plateau, which stayed constant for over 2 ns.…”
Section: V-cr Pbamentioning
confidence: 96%
“…The signal decayed and reached a plateau within a few ps. In a later TA study with improved time-resolution, 149 it was shown that the GSB decayed with ca. 200 fs and 1 ps time constants to the plateau, which stayed constant for over 2 ns.…”
Section: V-cr Pbamentioning
confidence: 96%
“…For example, it has been shown in Fe(acac) 3 that charge-transfer (CT) excitation leads to population of the lowest excited ligandfield state, corresponding to a change from S = 5/2 to S = 3/2 within < 400 fs [12]. Ultrafast ISC is known to happen in other systems, such as the wellstudied Fe(II) spin-crossover compounds where the S = 0 to S = 2 transition happens in less than 200 fs [13][14][15][16], in Cr(acac) 3 [17,18], and in thin films of Cr(III) molecule-based magnets [19,20].In transition metal complexes, multiple electronic potential energy surfaces intersect at high energies above the ground state due to the large density of states. The excited states are usually associated with a large change in geometry, meaning that there is a fast motion out of the Franck-Condon region along the steep potential energy surface towards the minimum of the excited state potential, which is why the change in spin can occur so quickly.…”
Section: Introductionmentioning
confidence: 99%
“…The different colors of the products (Figure 2) were generated from the metal−metal charge transfer (MMCT) between the transition-metal ions (Co 3+ ) and their counterpart transition-metal ions, which is in the visible light range, and from the ligand−metal charge transfer (LMCT) between cyanide ligands to the Co 3+ ions or vice versa, which is in the ultraviolet (UV) range. 36 Furthermore, the evolution of the particle shapes of Fe III HCCo, MnHCCo, and ZnHCCo can be further explained by the different methods of crystalline growth in path B, where the crystalline growth is enclosed by both {100} and {111} facets, but the growth ratio (R) along ⟨100⟩ to ⟨111⟩ determines the final particle morphologies. Thus, the polyhedral ZnHCCo is mainly truncated with both {100} and {111} facets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, crystals with stronger bonding energy result in larger particle sizes such as those of Fe III HCCo, MnHCCo, and ZnHCCo (Figure ). The different colors of the products (Figure ) were generated from the metal–metal charge transfer (MMCT) between the transition-metal ions (Co 3+ ) and their counterpart transition-metal ions, which is in the visible light range, and from the ligand–metal charge transfer (LMCT) between cyanide ligands to the Co 3+ ions or vice versa, which is in the ultraviolet (UV) range …”
Section: Resultsmentioning
confidence: 99%